O pátio escolar do ensino fundamental como ambiente de brincar segundo as crianças usuárias - Assis, Hellen Marques Barbosa Souza (2005)
The intention of the present study was to analyze the adequacy of the playground of elementary schools, according to the point of view of the child student, direct user of this type of environment, what estimated its critical in respect to these spaces and aimed at to contribute for its improvement. Many studies have analyzed the quality of the physical environment available for activities of leisure in specific places for children, focusing in the influence of the physical space in the interpersonal relationships and the comfort and satisfaction generated by the physical characteristics of these spaces. Concern with scholar environment, specially the interest on playgrounds, has been subject of recent studies; however, little attention has been given to the opinion of the user-child in relation to this school environment. In this inquiry of the playground of two state schools of 1ª to 4ª series of elementary school in the city of Piracicaba, SP, was used: assystematics observations, photographic register of the studied environments, interviews with child-users and behavioral mapping. The main subjects resulting from the analysis of the interviews content were: adaptation, density and interpersonal relationships, and infantile confinement. The results revealed the unsatisfactory conditions of the courtyards, in respect to person-environment relationship. The children demonstrated to be critical, creative and responsible when answering questions related to the quality of the school courtyard. This finding confirms previous studies and leads to the conclusion that the child, as the direct user, should be included as an excellent source of consultation in the planning of the constructed environment